Business Idea For KFC Malaysia: A Study of Potential Business Idea For KFC Holdings (Malaysia) Berhad - Muhammad Azriq Azlan Bin Zain Asman; Daisy Mui Hung Kee; Gonge Feng Yun; Huang Ze Xun; Tulika Thakur; Dheeraj Mehta (AIBPM Publisher, 2020)
KFC Malaysia is a food chain restaurants based in Malaysia which currently have over 700 restaurants around the peninsular and Sabah/Sarawak. This research is about new idea for KFC Malaysia to apply to their business. The target markets are wildly consist of social and economic. There are three main ideas to be implemented by KFC Malaysia in this research which is : 1- Self-service Counter, 2- Vegetarian-based dish, 3- Restaurants for the Homeless to Work. Financially, it will take a huge financial funding for these ideas to be implemented and be considered a success.